On the Levy-Baxter theorems for shot-noise fields. I - Buldygin, V. V.; Mel'nik, V. M.; Shportyuk, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We consider shot-noise fields generated by countably additive stochastically continuous homogeneous random measures with independent values on disjoint sets. We establish necessary and sufficient conditions under which the shot-noise fields possess the Levy-Baxter property on fixed and increasing parametric sets.